O Punk não é só para o seu Namorado: esfera pública alternativa, processos de identificação e testemunho na cena musical Riot Grrrl - Casadei, Eliza Bachega [UNESP] (My University, 2013)
The Riot Grrrl movement started in mid-90s and it consists of girls who use rock as a tool of feminist political struggle. Besides using music as a central element of political identity, this movement is also characterized by the formation of an alternative public sphere (formed by fanzines, blogs and e-zines) that functions both as a way to spread their music and as identification trigger mechanism in relation to their political causes. The aim of this article is to study the instruments that these feminists bands - that deviate from the traditional feminist political movements - use to create identification with their audience, especially from an empirical research of e-zines published by these bands and from the communicative action of their leaders in social networks. It is possible to note that, despite other identification mechanisms, testimonies works as a socialization link which marks the alternative public sphere composed by publications made by Riot Grrrls. The testimony serves as a powerful arranger of collective identities, since it is presupposed in the recognition of a world in common, allocating identity as performative action.

O movimento Riot Grrrl surgiu em meados dos anos 90 e é constituído por garotas que usam o rock como instrumento da luta política feminista. Além de utilizar a música como elemento identitário e político central, esse movimento também é caracterizado pela constituição de uma esfera pública alternativa (formada por fanzines, blogs e e-zines) que funciona tanto como um modo de divulgar as suas músicas quanto como disparadores de mecanismos de identificação em relação às suas causas políticas. O objetivo do presente trabalho é estudar os instrumentos que estas bandas feministas que se afastam dos movimentos políticos feministas tradicionais utilizam para criar identificação com o seu público, principalmente a partir de uma pesquisa empírica dos e-zines publicados por estas bandas e pela ação comunicativa de suas líderes nas redes sociais. É possível notar que, a despeito de outros mecanismos de identificação, é o testemunho que funciona como elo de sociabilização que marca a esfera pública alternativa composta pelas publicações feitas pelas Riot Grrrls. O testemunho funciona como um poderoso agenciador das identidades coletivas, uma vez que está pressuposto no reconhecimento de um mundo em comum, alocando a identidade enquanto ato performativo.
Punk is not just for your boyfriend: alternative public sphere, identification procedures and testimonies in the Riot Grrrl music scene
Keywords: Rock; Identities; Political struggle; Feminism; Alternative public sphere; Rock; Identidades; Luta política; Feminismo; Esfera pública alternativa